Effects of Microwave Irradiation on Dewaterability and Extracellular Polymeric Substances of Waste Activated Sludge. (1st March 2013) - Peng, Ge; Ye, Fenxia; Ye, Yangfang
Abstract : The effects of microwave irradiation on filterability and dewaterability of waste activated sludge measured by capillary suction time (CST) and dry solids in sludge cake were investigated. The results showed that the optimum irradiation time improved filterability, but that further increase of the time was detrimental. Dewaterability was enhanced significantly and increased with microwave time. Filterability and dewaterability were improved 25 to 28% and 1.3 times at the optimum times of 30 and 90 seconds for the sludge of 5 g total suspended solids (TSS)/L and 7 g TSS/L, respectively. The floc size decreased slightly. Loosely bound extracellular polymeric substances (LB‐EPS) decreased under optimum time, but tightly bound extracellular polymeric substances did not change significantly after short irradiation time. The results implied that LB‐EPS played a more important role in the observed changes of filterability and dewaterability and that the double‐layered extracellular polymeric substances extraction method showed marked implications to dewaterability.